Citizen scientists reveal small but concentrated amounts of fragmented microplastic on Arctic beaches - Pasolini, Franco; Walther, Bruno Andreas; Bergmann, Melanie (Frontiers in Environmental Science, 2023)
Plastic production and plastic waste have increased to such an extent that it has become globally ubiquitous. Recent research has highlighted that it has also invaded remote Polar Regions including the Arctic, where it is expected to accumulate over time due to transport from distant sources, rising local anthropogenic activities and increasing fragmentation of legacy ocean plastics to microplastics (plastic items < 5 mm). While a growing body of research has documented microplastics in the atmosphere, cryosphere, sea surface, water column, sediments and biota, contamination levels on Arctic beaches are poorly known. To fill this knowledge gap, we engaged citizen scientists participating in tourist cruises to sample beach sediments during shore visits on Svalbard, Norway.Following drying, sieving, and visual inspection of samples under a binocular microscope, putative plastic particles ≥ 1 mm were analysed by attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy. Plastic particles ≥ 1 mm were found in two out of 53 samples from 23 beaches (mean: 196.3 particles kg -1 and 147.4 particles L -1 ). These pollution levels could be due to our focus on plastic particles ≥ 1 mm as well as the relatively small sample sizes used during this initial phase of the project. In addition, the coarse substrate on most beaches might retain fewer plastic particles. The two samples with plastic particles ≥ 1 mm contained six polyester-epoxide particles and 4920 polypropylene fibres. The latter likely originated from a fishing net and points to possibly accelerated plastic fragmentation processes on Arctic beaches. Since fisheries-related debris is an important source of plastic on Svalbard, a build-up of microplastic quantities can be expected to burden Arctic ecosystems in addition to climate change unless efficient upstream action is taken to combat plastic pollution.